Measurements of inclusive and differential fiducial cross-sections of tt production with additional heavy-flavour jets in proton-proton collisions at vs =13 TeV with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Antel, Claire; Baas, Alessandra Edda; Andrei, George Victor; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Franchino, Silvia; Geisler, Manuel Patrice; Hanke, Paul; Jongmanns, Jan; et al. (Journal of high energy physics, 2019)
This paper presents measurements of tt¯tt¯ t\overline{t} production in association with additional b-jets in pp collisions at the LHC at a centre-of-mass energy of 13 TeV. The data were recorded with the ATLAS detector and correspond to an integrated luminosity of 36.1 fb−1. Fiducial cross-section measurements are performed in the dilepton and lepton-plus-jets tt¯tt¯ t\overline{t} decay channels. Results are presented at particle level in the form of inclusive cross-sections of tt¯tt¯ t\overline{t} final states with three and four b-jets as well as differential cross-sections as a function of global event properties and properties of b-jet pairs. The measured inclusive fiducial cross-sections generally exceed the tt¯bb¯¯tt¯bb¯ t\overline{t}b\overline{b} predictions from various next-to-leading-order matrix element calculations matched to a parton shower but are compatible within the total uncertainties. The experimental uncertainties are smaller than the uncertainties in the predictions. Comparisons of state-of-the-art theoretical predictions with the differential measurements are shown and good agreement with data is found for most of them. Open image in new window
The ATLAS collaboration: M. Aaboud, C.F. Anders, V. Andrei, C. Antel, A.E. Baas, A.E. Bolz, O. Brandt, M. Dunford, S. Franchino, M.P. Geisler, P. Hanke, J. Jongmanns, M. Kolb, A. Kugel, M. Lisovyi, H. F. Napolitano, D.I. Narrias Villar, A. Schoening, R. Stamen, P. Starovoitov, S. Suchek, J. Wang, S.M. Weber, M. Wessels, X. Yue [und weitere]
Gesehen am 26.06.2019